Aerodynamic Damping Prediction for Turbomachinery Based on Fluid-Structure Interaction with Modal Excitation - Jianxiong Li; Xiaodong Yang; Anping Hou; Yingxiu Chen; Manlu Li (Applied Sciences, 2019)
Aerodynamic damping predictions are critical when analyzing aeroelastic stability. A novel method has been developed to predict aerodynamic damping by employing two single time-domain simulations, specifically, one with the blade impulsed naturally in a vacuum and one with the blade impulsed in flow. The focus is on the aerodynamic damping prediction using modal excitation and the logarithmic decrement theory. The method is demonstrated by considering the first two bending modes with an inter-blade phase angle (IBPA) of 0° on a transonic compressor. The results show that the flutter boundary prediction is basically consistent with the experiment. The aerodynamic damping prediction with an IBPA of 180° is also performed, demonstrating that the method is suitable for different traveling wave mode representations. Furthermore, the influence of the amplitude of modal excitation and mechanical damping using the Rayleigh damping model for aerodynamic damping was also investigated by employing fluid-structure coupled simulations.